PENERAPAN METODE MIND MAPPING PADA PEMBELAJARAN MATEMATIKA - Rahma Faelasofi (Universitas Muhammadiyah Pringsewu, 2016)
The objectives of this research was to solve how to increase students learning mathematic achievments on the subject of statistic. This study aims to determine whether the students learning mathematic achievments of the student SMP Muhammadiyah 1 Gadingrejo in the academic year of 2014-2015 using learning method mind mapping on the subject of statistics can be higher than the students' learning mathematic achievments without using learning method mind mapping. This research is a quantitative approach. The population was all of the students in first grade of the SMP Muhammadiyah 1 Gadingrejo in the academic year of 2014- 2015. The samples of the research were taken by using the cluster random sampling technique. Based on hypothesis test, it can be included that there are differences in the average student learning achievments between using learning method mind mapping and learning method lecture on the subject of Statistics of the student in first grade of the SMP Muhammadiyah 1 Gadingrejo in the academic year of 2014-2015. Keywords: learning method mind mapping, students' learning mathematic achievments